2016
DOI: 10.1002/jcsm.12139
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ageing, physical activity, and pre‐frailty on skeletal muscle phenotype, mitochondrial content, and intramyocellular lipids in men

Abstract: BackgroundThe exact impact of ageing on skeletal muscle phenotype and mitochondrial and lipid content remains controversial, probably because physical activity, which greatly influences muscle physiology, is rarely accounted for. The present study was therefore designed to investigate the effects of ageing, physical activity, and pre‐frailty on skeletal muscle phenotype, and mitochondrial and intramyocellular lipid content in men.MethodsRecreationally active young adult (20–30 yo; YA); active (ACT) and sedenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
95
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 76 publications
(175 reference statements)
13
95
0
Order By: Relevance
“…47 The prevalence of sarcopenia in CHF patients is higher at 20% compared with control subjects of the same age. 50,51 In CHF, divergent anti-oxidative and metabolic but similar catabolic responses, i.e. 49 This particularly high incidence may be due to mitochondrial dysfunction combined with an abnormal energy metabolism and a transition of type I to type II myofibres.…”
Section: Chronic Heart Failure and Muscle Maintenancementioning
confidence: 99%
“…47 The prevalence of sarcopenia in CHF patients is higher at 20% compared with control subjects of the same age. 50,51 In CHF, divergent anti-oxidative and metabolic but similar catabolic responses, i.e. 49 This particularly high incidence may be due to mitochondrial dysfunction combined with an abnormal energy metabolism and a transition of type I to type II myofibres.…”
Section: Chronic Heart Failure and Muscle Maintenancementioning
confidence: 99%
“…[12][13][14][15][16][17] In the area of translational studies in the mechanisms of cachexia, studies were published on expression of spliced skeletal muscle genes, 18 along with scientific evaluations of skeletal muscle physiology, 19,20 growth, wasting, 21-23 preservation, 24,25 and regeneration. For the first time, the journal was seeing Cochrane reviews of the evidence base for interventions in cachexia and related fields coming through.…”
Section: By Methodologymentioning
confidence: 99%
“…
Introduction

The Journal of Cachexia, Sarcopenia and Muscle (JCSM) has progressed significantly in the past three years, not only both in terms of its number of submitted and published articles but also in terms of greater impact, reaching an Impact Factor of over 12 in the most recently published analyses by Clarivate Analytics. [12][13][14][15][16][17] In the area of translational studies in the mechanisms of cachexia, studies were published on expression of spliced skeletal muscle genes, 18 along with scientific evaluations of skeletal muscle physiology, 19,20 growth, wasting, 21-23 preservation, 24,25 and regeneration. We conducted an analysis of the types of publications in the respective medical sub-specialities that this major cachexia focussed journal, JCSM, has published in the last three calendar years and analysed trends within each sub-discipline.

…”
mentioning
confidence: 99%
“…Brierley et al similarly found a positive correlation between age and the presence of COX -fibres in VL biopsies from a sample of 49 participants aged 21-95 years, including no evidence of negative fibres in those aged under 64 years [11]. The overall activity of SDH on histochemistry has also been found to decline across adulthood, although maintenance of regular physical activity may prevent this decline [15].There has been less investigation of whether respiratory chain deficiency is more common in muscle in people with sarcopenia, as recently defined by the EWGSOP. However, a previous case series of nine patients at mean age 71 demonstrated that mitochondrial myopathy can present later in life, with biopsy findings showing a characteristic COX -/ SDH ++ pattern that was not seen in controls [16].…”
Section: Introductionmentioning
confidence: 94%